Alkali lignin derivative corrosion inhibitor as well as preparation method and application thereof

By forming micelles with alkali lignin and cetyl trimethylammonium bromide in anhydrous ethanol, the agglomeration problem of lignin corrosion inhibitors was solved, and an alkali lignin derivative corrosion inhibitor with high efficiency and anticorrosion effect was prepared. , significantly improves its anticorrosion performance in acidic environments.

CN119177451APending Publication Date: 2024-12-24GUANGZHOU UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411403415.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

As a corrosion inhibitor, lignin has agglomeration problem, which affects its anticorrosion effect in an acidic environment.

Method used

By mixing alkali lignin with cetyltrimethylammonium bromide in anhydrous ethanol, adding deionized water to form a stable micelle, using hydrophobic interactions and π-π bonds to drive their binding to form an ideal morphology micelles are used to prepare alkali lignin derivative corrosion inhibitors with excellent anticorrosion effects.

Benefits of technology

This method significantly improves the corrosion inhibition efficiency of alkali lignin derivative corrosion inhibitors, can achieve an anti-corrosion effect of more than 98% at room temperature, which is significantly better than existing corrosion inhibitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177451A_ABST
    Figure CN119177451A_ABST
Patent Text Reader

Abstract

The invention provides an alkali lignin derivative corrosion inhibitor as well as a preparation method and application thereof. The preparation method of the alkali lignin derivative corrosion inhibitor comprises the following steps: S1, adding an organic solvent into alkali lignin and hexadecyl trimethyl ammonium bromide, rapidly stirring and dissolving, then slowly stirring and dropwise adding deionized water to obtain a mixed solution; and S2, centrifuging and drying the mixed solution to obtain the alkali lignin derivative corrosion inhibitor. The alkali lignin derivative corrosion inhibitor disclosed by the invention has an excellent anti-corrosion effect on carbon steel in a hydrochloric acid solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion inhibitors, and in particular to an alkali lignin derivative corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] Metals play an important role in the production of various industries; among them, carbon steel has a low cost and good mechanical properties, so it has been widely used. Compared with stainless steels such as 304 and 316, carbon steel itself is not corrosion-resistant, especially in acidic environments such as oil and offshore operations. Metal corrosion has long been a concern for everyone, and a variety of methods have been developed to deal with it, such as sacrificial anode protection, external cathode electrical protection, external coating, and addition of corrosion inhibitors. The corrosion inhibitor method has a wide range of applications, so it is of great significance to develop corrosion inhibitors with good corrosion inhibition effects.

[0003] Lignin is an anionic surfactant that contains a large number of hydroxyl, carboxyl and benzene ring structures. Alkali lignin is an industrial byproduct obtained from lignin through alkaline pulping wastewater. As the second largest biomass material in the plant kingdom after cellulose, lignin has the characteristics of wide sources, large yields and low toxicity. The development of corrosion inhibitors using lignin as raw materials has great research significance and market value. Although the complexes generated by the reaction of hydroxyl and carboxyl groups of lignin with metal ions can adhere to the surface of carbon steel and prevent metal corrosion, and the hydrophobic benzene rings will be adsorbed on the hydrophobic carbon steel surface to form a certain protective effect, lignin itself is easy to agglomerate through its own van der Waals force and π-π bonds, which seriously affects its corrosion inhibition effect.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide an alkali lignin derivative corrosion inhibitor and a preparation method and application thereof. The alkali lignin derivative corrosion inhibitor has an excellent anti-corrosion effect on carbon steel in a hydrochloric acid solution.

[0006] The present invention provides a method for preparing an alkali lignin derivative corrosion inhibitor, comprising the following steps:

[0007] S1: adding an organic solvent to alkali lignin (AL) and cetyltrimethylammonium bromide (CTAB), rapidly stirring to dissolve, then slowly stirring and dropping deionized water to obtain a mixed solution;

[0008] S2: Centrifuge and dry the mixed solution to obtain an alkali lignin derivative corrosion inhibitor.

[0009] In step S1, the mass ratio of alkali lignin to hexadecyltrimethylammonium bromide is 2:(0.3-0.5); the organic solvent is anhydrous ethanol; the volume ratio of anhydrous ethanol to deionized water is 1:(2-4), preferably 1:(2-3); the stirring speed during rapid stirring is 2500-3500r / min, and the stirring time is 20-40min; the stirring speed during slow stirring is 300-500r / min, and the stirring time is 20-40min.

[0010] In step S2, the rotation speed during centrifugation is 2800-3200 r / min, and the centrifugation time is 40-80 min; the temperature during drying is 40-60° C., and the drying time is 40-50 h.

[0011] In step S1, anhydrous ethanol is added to dissolve alkali lignin and hexadecyltrimethylammonium bromide; rapid stirring is to fully dissolve the alkali lignin and hexadecyltrimethylammonium bromide; deionized water is added dropwise and the volume ratio of anhydrous ethanol to deionized water is controlled because when the volume ratio of deionized water to anhydrous ethanol is greater than the above-mentioned specific value, the two raw materials will form stable micelles; centrifugation in step S2 utilizes the strong centrifugal force generated when an object rotates at high speed to cause the product placed in the rotating body to settle, thereby separating the product from the incompletely dissolved alkali lignin; and drying is to evaporate the solution to obtain a relatively purified corrosion inhibitor prepared based on alkali lignin.

[0012] In the above preparation method, alkali lignin and hexadecyltrimethylammonium bromide are highly dispersed in anhydrous ethanol. By changing the solvent environment and reducing the solubility of the solute, that is, adding deionized water to the solution, the original good solvent is turned into a poor solvent. Alkali lignin and hexadecyltrimethylammonium bromide begin to combine in the solution due to hydrophobic interaction, π-π bond stacking, hydrogen bonding, etc., wherein the quaternary ammonium salt group of hexadecyltrimethylammonium bromide is grafted onto the phenolic hydroxyl group of alkali lignin to form micelles with an ideal morphology.

[0013] The invention also provides an alkali lignin derivative corrosion inhibitor, which is prepared according to the above preparation method.

[0014] The present invention also provides application of the alkali lignin derivative corrosion inhibitor in corrosion prevention.

[0015] Specifically, the anti-corrosion is to prevent the corrosion of Q235 steel in a hydrochloric acid solution; wherein the concentration of hydrochloric acid in the hydrochloric acid solution is 1 mol / L, and the concentration of the alkali lignin derivative corrosion inhibitor in the hydrochloric acid solution is 10-500 ppm.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects:

[0017] 1. Lignin is the second most abundant biomass in nature and has a wide range of sources, but its development and utilization are insufficient, resulting in a large amount of waste; the preparation method of the present invention uses alkali lignin as a raw material, providing a new direction for the application of lignin and alkali lignin.

[0018] 2. The preparation method of the present invention has the advantages of simple process flow, rapid synthesis process, safe production operation, and green and pollution-free process. The corrosion inhibitor prepared by the preparation method is a high-efficiency corrosion inhibitor, which is a brown powder at room temperature, easily soluble in water, and exhibits excellent corrosion inhibition effect. The corrosion inhibition efficiency can reach more than 98%, which is more significant than many existing corrosion inhibitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 The ultraviolet absorption spectra of the alkali lignin, hexadecyltrimethylammonium bromide and alkali lignin derivative corrosion inhibitor of Example 1;

[0021] Figure 2 It is a schematic diagram of the structure of the three-electrode test system of Experimental Example 1;

[0022] Figure 3 The Nyquist plots of the alkali lignin derivative corrosion inhibitor of Example 1 with different concentrations immersed in a 1 mol / L hydrochloric acid solution for 2 hours;

[0023] Figure 4 The Bode diagrams of the alkali lignin derivative corrosion inhibitors of Example 1 with different concentrations immersed in 1 mol / L hydrochloric acid solution for 2 hours;

[0024] Figure 5 The Bode diagrams of the alkali lignin derivative corrosion inhibitors of Example 1 with different concentrations immersed in 1 mol / L hydrochloric acid solution for 2 hours;

[0025] Figure 6 is the equivalent circuit diagram of electrochemical impedance spectroscopy;

[0026] Figure 7 The polarization curves of the alkali lignin derivative corrosion inhibitor of Example 1 with different concentrations immersed in 1 mol / L hydrochloric acid solution for 2 hours;

[0027] Figure 8The Nyquist plot of the alkali lignin corrosion inhibitor of Comparative Example 1 immersed in a 1 mol / L hydrochloric acid solution for 2 hours;

[0028] Fig. 9 The Bode diagram of the alkali lignin corrosion inhibitor of Comparative Example 1 immersed in a 1 mol / L hydrochloric acid solution for 2 hours;

[0029] Fig.10 This is the Bode diagram of the alkali lignin corrosion inhibitor of Comparative Example 1 immersed in 1 mol / L hydrochloric acid solution for 2 hours. DETAILED DESCRIPTION

[0030] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0031] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] The preparation method of the alkali lignin derivative corrosion inhibitor of this embodiment comprises the following steps:

[0035] (1) 2 g of alkali lignin (AL) and 0.364 g of hexadecyltrimethylammonium bromide (CATB) were mixed and then 20 mL of anhydrous ethanol was added to obtain a solution;

[0036] (2) The above solution was rapidly stirred at 3000 r / min for 30 min, and then slowly stirred at 400 r / min, while 50 mL of deionized water was added dropwise to the solution at a rate of 1.76 mL / min, and the slow stirring time was 30 min to obtain a mixed solution;

[0037] (3) The mixed solution was centrifuged at 3000 r / min for 60 min, and then dried at 50° C. for 45 h to obtain an alkali lignin derivative corrosion inhibitor (denoted as AL-CATB).

[0038] Test Example 1

[0039] The raw materials alkali lignin (AL), hexadecyltrimethylammonium bromide (CATB) and the product alkali lignin derivative corrosion inhibitor (AL-CATB) of Example 1 were subjected to infrared absorption spectrum test, and the obtained ultraviolet spectrum image was as follows: Figure 1 shown.

[0040] from Figure 1 As can be seen from the FTIR spectrum, the infrared characteristic peak of the copolymer can be observed at 3407 cm -1 The stretching vibration of OH bonds in the wavelength range and CTAB at 2849cm -1 The characteristic absorption of CN bonds within the wavelength range indicates that the AL-CTAB copolymer was successfully synthesized by this method.

[0041] Test Example 2

[0042] The alkali lignin derivative corrosion inhibitor prepared in Example 1 was evaluated by electrochemical method. The electrochemical workstation was CS310H, combined with Figure 2 As shown, the test adopts a three-electrode system: the working electrode is made of Q235 carbon steel, the reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum electrode. The Q235 carbon steel is encapsulated into a cylindrical electrode with epoxy resin, and the electrode is encapsulated on one end of the epoxy and welded with a copper wire to lead out the conduction circuit. The exposed area of ​​the working electrode is about 3.14cm 2 Except for the exposed surface in contact with the solution, the other end surfaces are encapsulated with epoxy resin. The exposed surface of the working electrode is polished with 240 mesh, 400 mesh, 800 mesh and 1200 mesh SiC sandpaper, then cleaned with deionized water and anhydrous ethanol, dried with cold air and placed in a vacuum dryer for use. The AC impedance test frequency is 10 -2 -10 4 Hz, amplitude is 10mV. The experiment was carried out in 1mol / L hydrochloric acid solution, and the experimental temperature was 25℃. The test was started after the open circuit potential reached stability. The data obtained by fitting the AC impedance spectrum through the equivalent circuit diagram, and the corrosion inhibition efficiency was calculated using the following formula:

[0043]

[0044] In the formula: IE EIS is the corrosion inhibition efficiency, %; R 0 ct is the charge transfer resistance of the blank group, Ω; R ctis the charge transfer resistance after adding corrosion inhibitor, Ω.

[0045] The AC impedance spectra of Q235 carbon steel in 1 mol / L hydrochloric acid solution with different concentrations of alkali lignin derivative corrosion inhibitor were obtained. Figure 3-Figure 5 shown.

[0046] Use as Figure 6 The equivalent circuit diagram shown is used to fit the above impedance spectrum, and the fitting data is shown in Table 1; where R s is the solution resistance; CPE is the constant phase element; R f is the membrane resistance; R ct is the charge transfer resistance; η is the corrosion inhibition efficiency.

[0047] Table 1 AC impedance spectrum fitting results of Q235 carbon steel in 1 mol / L hydrochloric acid solution with different concentrations of alkali lignin derivative inhibitors added for 2 h

[0048]

[0049]

[0050] As shown in Table 1, the charge transfer resistance of the blank group without corrosion inhibitor is small, indicating that serious corrosion has occurred on the metal surface. When different concentrations of alkali lignin derivative corrosion inhibitors are added, the charge transfer resistance increases significantly, indicating that the alkali lignin derivative corrosion inhibitor can effectively inhibit the corrosion of metals. When the corrosion inhibitor concentration is 500ppm, the corrosion inhibition efficiency of the alkali lignin derivative corrosion inhibitor is the best, and the corrosion inhibition efficiency is as high as 99.03% when immersed for 2h.

[0051] The polarization curves of Q235 carbon steel in 1 mol / L hydrochloric acid solution with different concentrations of alkali lignin derivative corrosion inhibitor were measured. The scanning range was about -150 mV to 230 mV relative to the open circuit potential, the scanning rate was 0.5 mV / s, and the sampling frequency was 1 Hz. Figure 7 shown.

[0052] The corrosion inhibition efficiency is calculated using the following formula:

[0053]

[0054] Where: η is the corrosion inhibition efficiency, %; I0 is the corrosion current of the blank control group after immersion for 2 hours, Amp / cm 2 ; is the corrosion current after immersion for 2 hours after adding the alkali lignin derivative-based corrosion inhibitor, Amp / cm 2 .

[0055] The fitting results of the polarization curves are shown in Table 2. ois the corrosion potential, Volts; I o is the corrosion current, Amp / cm 2 ; η is the corrosion inhibition efficiency, %.

[0056] Table 2 Fitting results of polarization curves of Q235 carbon steel after immersion in 1 mol / L hydrochloric acid solution with different concentrations of alkali lignin derivative corrosion inhibitor for 24 h

[0057]

[0058]

[0059] As shown in Table 2, after adding the alkali lignin derivative corrosion inhibitor, the corrosion potential of Q235 carbon steel shifted positively and the corrosion current decreased, indicating that the alkali lignin derivative corrosion inhibitor showed a significant inhibitory effect. When the corrosion inhibitor concentration was 500ppm, the corrosion inhibition efficiency reached 99.13%.

[0060] Example 2

[0061] The preparation method of the alkali lignin derivative corrosion inhibitor of this embodiment comprises the following steps:

[0062] (1) 2 g of alkali lignin and 0.3 g of hexadecyltrimethylammonium bromide were mixed and then 20 mL of anhydrous ethanol was added to obtain a solution;

[0063] (2) The above solution was rapidly stirred at 2500 r / min for 40 min, and then slowly stirred at 300 r / min, while 40 mL of deionized water was added dropwise to the solution at a speed of 1.32 rpm, and the slow stirring time was 20 min to obtain a mixed solution;

[0064] (3) The mixed solution was centrifuged at 2800 r / min for 80 min, and then dried at 40° C. for 50 h to obtain an alkali lignin derivative corrosion inhibitor.

[0065] The alkali lignin derivative corrosion inhibitor of this embodiment was evaluated using the method of Test Example 2; the results showed that the corrosion inhibition efficiency η of the alkali lignin derivative corrosion inhibitor of this embodiment was 98.8% when the corrosion inhibitor concentration was 500 ppm.

[0066] Example 3

[0067] The preparation method of the alkali lignin derivative corrosion inhibitor of this embodiment comprises the following steps:

[0068] (1) 2 g of alkali lignin and 0.5 g of hexadecyltrimethylammonium bromide were mixed and then 20 mL of anhydrous ethanol was added to obtain a solution;

[0069] (2) The above solution was rapidly stirred at 3500 r / min for 20 min, and then slowly stirred at 500 r / min, while 60 mL of deionized water was added dropwise to the solution at a speed of 2.2 rpm, and the slow stirring time was 40 min to obtain a mixed solution;

[0070] (3) The mixed solution was centrifuged at 3200 r / min for 40 min, and then dried at 60° C. for 40 h to obtain an alkali lignin derivative corrosion inhibitor.

[0071] The alkali lignin derivative corrosion inhibitor of this embodiment was evaluated using the method of Test Example 2; the results showed that the corrosion inhibition efficiency η of the alkali lignin derivative corrosion inhibitor of this embodiment was 98.9% when the corrosion inhibitor concentration was 500 ppm.

[0072] Example 4

[0073] The preparation method of the alkali lignin derivative corrosion inhibitor of this embodiment comprises the following steps:

[0074] (1) 2 g of alkali lignin and 0.364 g of hexadecyltrimethylammonium bromide were mixed and then 20 mL of anhydrous ethanol was added to obtain a solution;

[0075] (2) the solution was rapidly stirred at 3000 r / min for 30 min, and then slowly stirred at 400 r / min, while 80 mL of deionized water was added dropwise to the solution at a speed of 2 rpm to obtain a mixed solution;

[0076] (3) The mixed solution was centrifuged at 3000 r / min for 60 min, and then dried at 50° C. for 45 h to obtain an alkali lignin derivative corrosion inhibitor.

[0077] The alkali lignin derivative corrosion inhibitor of this example was evaluated using the method of Test Example 2; the results showed that the corrosion inhibition efficiency η of the alkali lignin derivative corrosion inhibitor of this example was 94.4% when the corrosion inhibitor concentration was 500 ppm.

[0078] Comparative Example 1

[0079] Q235 carbon steel (φ=2cm) was used, polished with 240 mesh, 400 mesh, 800 mesh, and 1200 mesh SiC sandpaper, degreased with ethanol, and then dried with a hair dryer. One surface (10×10mm) of the treated sample was retained, and the remaining surfaces were sealed with high-temperature epoxy resin, and immersed in a 1 mol / L hydrochloric acid solution with 500ppm of alkali lignin (AL). After immersion for 2h, the electrochemical impedance spectrum in the solution was measured using the method of Experimental Example 2. The results are shown in Figure 8-Figure 10 .

[0080] Use as Figure 6The equivalent circuit diagram shown is used to fit the above impedance spectrum, and the fitting data is shown in Table 3; where R s is the solution resistance; CPE is the constant phase element; R f is the membrane resistance; R ct is the charge transfer resistance; η is the corrosion inhibition efficiency.

[0081] Table 3 Fitting results of AC impedance spectrum of Q235 carbon steel in 1 mol / L hydrochloric acid solution with 500 ppm alkali lignin inhibitor

[0082]

[0083] It can be seen from Table 3 that after adding alkali lignin, the charge transfer resistance increases and the corrosion inhibition efficiency is 75.18%. The results show that in a 1 mol / L hydrochloric acid solution environment, adding the alkali lignin corrosion inhibitor of Comparative Example 1 has an effect on Q235 carbon steel but it is not significant, and the corrosion inhibition effect is significantly weaker than that of the alkali lignin derivative corrosion inhibitor.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an alkali lignin derivative corrosion inhibitor, characterized in that: The steps include: S1: adding an organic solvent to alkali lignin and hexadecyltrimethylammonium bromide, rapidly stirring to dissolve, then slowly stirring and dropping deionized water to obtain a mixed solution; S2: Centrifuge and dry the mixed solution to obtain an alkali lignin derivative corrosion inhibitor.

2. The preparation method according to claim 1, characterized in that: The mass ratio of alkali lignin to hexadecyltrimethylammonium bromide is 2:(0.3-0.5).

3. The preparation method according to claim 1, characterized in that: The organic solvent is anhydrous ethanol; the volume ratio of anhydrous ethanol to deionized water is 1:(2-4).

4. The preparation method according to claim 1, characterized in that: The stirring speed during rapid stirring is 2500-3500r / min, and the stirring time is 20-40min.

5. The preparation method according to claim 1, characterized in that: The stirring speed during slow stirring is 300-500r / min, and the stirring time is 20-40min.

6. The preparation method according to claim 1, characterized in that: The speed during centrifugation is 2800-3200r / min, and the centrifugation time is 40-80min.

7. The preparation method according to claim 1, characterized in that: The drying temperature is 40-60°C and the drying time is 40-50h.

8. An alkali lignin derivative corrosion inhibitor, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 7.

9. Use of the alkali lignin derivative corrosion inhibitor according to claim 8 in corrosion protection.

10. The use according to claim 9, characterized in that: The anti-corrosion is to prevent the corrosion of Q235 steel in a hydrochloric acid solution; wherein the concentration of hydrochloric acid in the hydrochloric acid solution is 1 mol / L, and the concentration of the alkali lignin derivative corrosion inhibitor in the hydrochloric acid solution is 10-500 ppm.

Citation Information

Cited By

  • Preparation method of aminated lignin metal corrosion inhibitor suitable for strong acid condition

    CN120924981A